The effects of nalmefene on the impulsive and reflective system in alcohol use disorder: a resting-state fMRI study - Grundinger, Nadja; Gerhardt, Sarah; Karl, Damian; Mann, Karl; Kiefer, Falk; Vollstädt-Klein, Sabine (Psychopharmacology, 2022)
Central aspects of alcohol use disorder (AUD) are the irresistible desire for alcohol and impaired control over its intake. According to the triadic neurocognitive model of addiction, this arises from aberrant functioning of different neural and cognitive systems: an impulsive system, a reflective system, and the abnormal dynamics between both systems based on an insular-dependent system.